ChemInform Abstract: Synthesis and Tautomerism of Spiro‐Pyrazolines. Issue 37 (16th September 2014) - Dadiboyena, Sureshbabu; Valente, Edward J.; Hamme, Ashton T. II
Abstract Upon addition of TFA spiropyrazoline (III) exhibits an imine‐enamine tautorism which is evidenced by X‐ray analysis of (III) as well as NMR studies.